Composition, Distribution, and Diversity of Gastropod Species in The Estuarine Waters of Kaiyasa and Oba Village, Tidore Islands City, North Maluku - Ramili, Yunita; Marus, Ikbal; Barawis, Nurul Asmania H.; Umasangaji, Halikuddin (Agrikan Jurnal Agribisnis Perikanan, 2025)
Estuaries are one of the habitats for gastropods that have not been widely explored in North Maluku. This study aims at assessing the ecological conditions of gastropods in the estuarine waters including their composition, distribution, density, and species diversity. The study was conducted in August 2024 in the estuarine waters of Kaiyasa Village (Station 1) and Oba Village (Station 2). Data collection was carried out using the Quadratic Linear Transect Method. The results of this study found six species of gastropods with the highest composition found at Station 1 as 6 species, namely Faunus ater, Telescopium telescopium, Terebralia palustris, Cerithium coralium, Nassarius olivaceus, and Chicoreus capucinus compared to Station 2 as two species namely F. ater and T. palustris. F. ater which dominated both research stations since they were found in large numbers, namely 342 individuals (93%) at Station 1 and 299 individuals (98%) at Station 2. F. ater also had the highest density values of all species of gastropods found, namely 19.00 ind/m2 (Station 1) and 16.61 ind/m2 (Station 2), while C. coralium and C. capucinus have the lowest density values of 0.11 ind/m2. In general, the ecological conditions of gastropods at both research stations indicate a relatively low level of species diversity (H’ = 0.1 – 0.34), with low species evenness (E = 0.14 – 0.19), and indicated the dominance of certain species (C = 0.87 – 0.96), namely F. ater. The quality of the estuary water environment at both stations was still suitable for supporting gastropod life.